Penguatan Kompetensi Sosio-Kultural Pegawai Kementerian Pendayagunaan Aparatur Negara/Reformasi Birokrasi - Faisal Ahmadani (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2024)
Accelerating bureaucratic reform to realize world-class government administration requires various efforts implemented conceptually, especially in developing the competence of the State Civil Apparatus. Education and training to develop national defense awareness in the scope of work is one of the efforts to strengthen the socio-cultural competence of the State Civil Apparatus, especially for employees of the Ministry of State Apparatus Empowerment/Bureaucratic Reform as the leading sector of bureaucratic reform. This research is a qualitative study which aims to determine the outcome of the process of developing attitudes and behavior as well as instilling the basic values of defending the country as a result of implementing the training, especially in the formation of initial non-physical national defense capabilities as soft competency which contributes to strengthening the participants' socio- cultural competencies. This research concludes that the participation of the State Civil Apparatus from other ministries/institutions in training needs to be considered so that the utilization of state apparatus with awareness of defending the state can contribute to the acceleration of bureaucratic reform. This research concludes that the participation of the State Civil Apparatus from other ministries/institutions in training needs to be considered so that the utilization of state apparatus with awareness of defending the state can contribute to the acceleration of bureaucratic reform. slot gacor slot gacor slot gacor slot gacor slot gacor